Betaine supplementation improves CrossFit performance and increases testosterone levels, but has no influence on Wingate power: randomized crossover trial - Emilia Zawieja; Krzysztof Durkalec-Michalski; Marcin Sadowski; Natalia Główka; Agata Chmurzynska (Taylor & Francis Group, 2023)
Background Because betaine (BET) supplementation may improve muscular strength and endurance, it seems plausible that BET will also influence CrossFit performance (CF). Purpose The aim of this study was to evaluate the effects of three weeks of BET supplementation on body composition, CF performance, muscle power in the Wingate anaerobic test (WAnT), and the concentrations of selected hormones. The secondary aims were to analyze the effectiveness of two different BET doses (2.5 and 5.0 g/d) and their interaction with the methylenetetrahydrofolate reductase (MTHFR) genotype. Methods The study was designed in a double-blinded randomized cross-over fashion. Forty-three CF practitioners completed the entire study. CF performance was measured using the Fight Gone Bad (FGB) workout and muscle power was evaluated in a 30-second WAnT. Body composition was determined by air-displacement plethysmography. Blood was drawn to assess hormone concentrations. The C677T single nucleotide polymorphism (rs180113) in the MTHFR gene was analyzed. Results FGB total improved with BET by 8.7 ± 13.6% (p < 0.001), but no significant changes were observed with placebo (- 0.4 ± 10.0%, p = 0.128). No changes were also observed in WAnT and body composition. After BET supplementation testosterone concentration increased by 7.0 ± 15.4% with BET (p = 0.046) (no change with placebo: 1.5 ± 19.6%, p = 0.884) but had no effect on concentrations of insulin-like growth factor or cortisol. Finally, there were no significant interactions between MTHFR genotype and BET dose in any outcome. Conclusions BET supplementation may improve CF performance and increase testosterone concentration. However, there was no evidence of a difference between dosages (2.5 and 5.0 g/d) and MTHFR genotypes. The trial was registered on clinicaltrials.gov (NCT03702205) on 10 October 2018.